Training for Making Dishwashing Soap for Youth in Gubuk Baru Hamlet, Central Lombok Regency - Urwatil Wutqo Amry; Baiq Anita Febriana; Renda Suri Pratimi; Rahimal Khair (LPPM Institut Studi Islam Sunan Doe, 2022)
Lack of knowledge of village youth about chemicals and how to process them has closed business opportunities in Dusun Gubuk Baru, Tanank Beak Village, Kec. North Batukliang. Therefore, rural youth need training to process these chemicals into a product that is safe for the environment. Empowerment of the New Hut Youth, most of whom work as casual daily laborers and farmers. So that with this training in making grandson dish soap, it has the potential to open up business opportunities for youth in Dusun Gubuk Baru. The result of this training is that young people in Dusun Gubuk Baru can properly process several chemicals and materials from nature into dish soap that is ready to be marketed and of course it is more environmentally friendly. The impact of the training we provide is that the mindset of the young huts has changed a little from what they initially thought that chemistry was only about bombs, now they think that chemistry is very fun because there are many things that can be done or made by mixing chemicals. One example is the manufacture of dish soap.